PENGEMBANGAN ALUMINUM MATRIX COMPOSITE DENGAN MENGGUNAKAN PENGUAT SERBUK HASIL SINTESIS LIMBAH ABU TERBANG BATUBARA YANG DIPROSES DENGAN REAKSI CARBOTHERMAL REDUCTION - , Sulardjaka, ST.,MT., Prof. Ir. Jamasri, Ph.D. ([Yogyakarta] : Universitas Gadjah Mada, 2011)
Fly ash is a by product of the burning process at coal-fired power plant. Fly ash is obtained by electrostatic or mechanical precipitation from the flue gases of furnaces fired with pulverized coal. The current annual production of coal ash world wide is estimated around 600 millions tons, with fly ash constituting about 500 millions tons. Suralaya power plant, one of the Indonesiaâs power plants that uses coal, produces about 0.2 millions tons fly ash in 2005. A substantial amount of fly ash is still disposed of in landfill. Increasing the amount of fly ash being reutilized will be minimized disposal cost, less area is reserved for disposal and replaced some scarce or expensive natural resources. The addition of fly ash into aluminum as reinforcement can potentially reduce the production cost and density of aluminum. However, mechanical properties of aluminum matrix composite reinforced by fly ash (MMC ALFA) have some limitations due to the characteristic of fly ash. In this study, a carbothermal reduction process of fly ash and activated carbon powder with particle size < 32 Î¼m. The objective of carbothermal reduction process of fly ash and activated carbon powder is to react SiO2 and carbon to from SiC. The carbothermal reduction process of fly ash and activated carbon powder was performed prior to produce MMC ALFA. Carbothermal reduction process has been carried out at temperature 1200 o C, 1300 o C and 1400 o C under vacuum. Holding time of the synthesis process was 2 hours. Synthesized products were examined by X-ray powder diffraction (XRD) using Cu KÎ± radiation, Fourier transformation infrared spectrometer (FTIR) and SEM fitted with EDS. The amount of Î²-SiC yield in each process was estimated by comparing the relative height of the Î²-SiC diffraction peaks with that of all diffraction peaks. Cycling synthesis process has been developed for increasing SiC yield at the temperature synthesis 1300 o C and 1400 o C. After synthesis process, synthesized product was used as reinforcement powder on aluminum matrix composite. Metal matrix composite was prepared by powder metallurgy technique. Commercially pure (99,9 %) aluminum fine powder supplied by Merck was used in this experiment. Aluminum fine powder was mixed in turbula mill with 5, 10 and 15 % weight fraction of the carbothermal reduced product, and then uniaxially compacted at pressure of 300 MPa. The green body was sintered in argon atmosphere at temperature 550 and 600 o C for 2 hours. Flexural properties was tested by four point flexural test based on ASTM C1161 standard. Hardness of MMC product was tested by brinell hardness test. Wear resistance of MMC was tested by Ogoshi High Speed Universal Wear Testing Machine. Density of composite was tested based Archimedes method. The experiment results show that carbothermal reduction process can produce Î²-SiC powder. Î²-SiC successfully synthesizes at temperature 1300 o C for 2 hours. Percentage of Î²-SiC yield increases by the cycling synthesis. The cycling synthesis process produces new contact point between silicon and carbon and promotes the diffusion rate. Carbothermally reduced of fly ash contains : 53.5 % SiC